A pretensão popular de tutela dos direitos fundamentais sociais por intermédio da função jurisdicional do poder público - Silva, Adriano Luís de Almeida (2008)
The work is developed through a study about historic origin of the principle of segregation of the powers until its modern functional concept, aiming at demonstrating that it is not incompatible with the popular control of the effectiveness of the fundamental social rights through judicial function. Following, it was tried to give evidence to which must be the juridical of the state financial limitations as a main factor to the fundamental social rights, and the way they have to be faced in the process ambient. Finally, the work was submitted to the norms of the fundamental social rights with the approval of the juridical concept of the subjective right in order to give them the attribute of subjective pretension.